Characteristics and Outcomes of Younger Adults with Embolic Stroke of Undetermined Source (ESUS): A Retrospective Study - Ali M. Al Khathaami; Bayan Al Bdah; Abdulmjeed Alnosair; Abdulkarim Alturki; Rayan Alrebdi; Shorug Alwayili; Sulaiman Alhamzah; Fahad A. M. AlKhathaami; Nasser Alotaibi (Stroke Research and Treatment)
Introduction. Embolic stroke of undetermined source (ESUS) in younger adults may have different risk factors compared with ESUS in elderly, and the approach to ESUS in young adults may require new therapies. We aimed to investigate the characteristics and outcomes in younger adults with ESUS at a single centre in Saudi Arabia. Patients and Methods. A retrospective study was conducted using the medical records of younger adults with ESUS according to the criteria of the Cryptogenic Stroke/ESUS International Working Group. Younger adults (aged ≤50 years) with ESUS were compared with older patients, on admission and discharge from hospital, using the modified Rankin scale (mRS) and the National Institute of Health Stroke Scale (NIHSS). Results. Among 147 patients with ESUS, 39 (26.5%) were younger adults. Younger adults compared with older adults with ESUS had fewer vascular risk factors, including lower rates of hypertension (43.6% vs. 70.3%; P=0.004), diabetes (35.9% vs. 57.4%; P=0.03), and dyslipidaemia (12.8% vs. 28.7%; P=0.05). There was no significant difference in poor outcome at discharge (defined as mRS > 2), which was observed in 17.9% of younger adults and 28.7% of older adults. Further, there were no significant differences in stroke severity at discharge (NIHSS score ≤5) or median length of stay. Discussion. Although the outcomes of ESUS do not differ between younger and older patients, younger patients have fewer identified risk factors. Conclusion. This study showed that 26.5% of patients with ESUS were aged ≤50  years. Although younger adults with ESUS had fewer risk factors, there were no significant differences in neurologic disability or mortality at discharge, stroke severity, or median length of stay.